A Distinctive Clinical Phenotype of Discoid Lupus Erythematosus in Papuanese Women: A 5-Year Analysis of Dyspigmentation, Scarring, and Malar Predilection - Inneke Viviane Sumolang; Astrina Rosaria Indah; Timothy Verellino Reba; Aryani Adji; Paulus Mario Christopher (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Discoid lupus erythematosus (DLE), the most common form of chronic cutaneous lupus, exhibits significant clinical variability influenced by ethnicity. While disparities in presentation are recognized, data from unique indigenous populations such as the Papuanese in East Indonesia remain scarce. This study aimed to characterize the clinical and sociodemographic features of DLE in this specific cohort to identify its potentially distinctive phenotype. Methods: A five-year retrospective analysis of clinical databases was conducted at the Department of Dermatology and Venereology at a tertiary referral hospital in Jayapura, Papua, Indonesia. All patients clinically diagnosed with DLE by board-certified dermatovenereologists between January 2019 and December 2023 were included. Sociodemographic and clinical data, including lesion morphology, location, and management, were systematically collected and analyzed using descriptive statistics. Results: A total of 22 patients meeting the criteria were identified. The cohort demonstrated remarkable homogeneity; all patients were of Papuanese ethnicity and female (100.0%). The majority were in the 26-35 age group (40.9%), with a mean age of 29.4 years, and half were farmers (50.0%). Clinically, lesions were universally present on the nose and/or malar area (100.0%). The most common morphological triad was dyspigmentation, scarring, and telangiectasia, observed in 81.8% of patients. All patients reported photosensitivity and were managed with photoprotection and topical steroids. Conclusion: DLE I n Papuanese women presents as a distinctive, highly uniform clinical phenotype characterized by an exclusive female predilection, a strong association with sun exposure, and a universal malar distribution with a high propensity for disfiguring dyspigmentation and scarring. These findings underscore the necessity of culturally competent, early, and aggressive management strategies to mitigate long-term sequelae in this vulnerable population.